Analisis Komunikasi Digital Gereja Kristus Yesus Sunter Dalam Pelayanan Jemaat di Media Sosial - Wijaya, Tommy (Prisani Cendekia Institute, 2024)
The Church of Jesus Christ (commonly known as Gereja Kristus Yesus or GKY) Sunter is a Protestant Christian church located in Indonesia. Its foundation rests on the belief that Jesus Christ serves as the head of the church. In this digital age, many churches, including The Church of Jesus Christ (Gereja Kristus Yesus or GKY) Sunter, have fully embraced digital communication. The Church of Jesus Christ (Gereja Kristus Yesus or GKY) Sunter is actively digitizing information related to church activities and sharing content across various social media platforms. The research conducted on this topic employs data collection methods such as observation, interviews, and literature review. The qualitative analysis is based on new media theory by Pierre Levy. The findings indicate that GKY Sunter employs several forms of digital communication, including e-mail, websites, and social media. In their ministry to the congregation, GKY Sunter actively utilizes new media platforms such as Instagram, TikTok, YouTube, and WhatsApp. These channels facilitate easier access for congregants to stay informed about church activities.The Church of Jesus Christ (commonly known as Gereja Kristus Yesus or GKY) Sunter is a Protestant Christian church located in Indonesia. Its foundation rests on the belief that Jesus Christ serves as the head of the church. In this digital age, many churches, including The Church of Jesus Christ (Gereja Kristus Yesus or GKY) Sunter, have fully embraced digital communication. The Church of Jesus Christ (Gereja Kristus Yesus or GKY) Sunter is actively digitizing information related to church activities and sharing content across various social media platforms. The research conducted on this topic employs data collection methods such as observation, interviews, and literature review. The qualitative analysis is based on new media theory by Pierre Levy. The findings indicate that GKY Sunter employs several forms of digital communication, including e-mail, websites, and social media. In their ministry to the congregation, GKY Sunter actively utilizes new media platforms such as Instagram, TikTok, YouTube, and WhatsApp. These channels facilitate easier access for congregants to stay informed about church activities.